Language and ethnicity in Central and Eastern Europe: Some theoretical aspects - George Schopflin (Politologija)
This article presents a favourable theoretical analysis of the political problem of high profile which acutely touches Central and Eastern Europe – the ethnic problem. The outstanding role in delimiting ethnic dependence and conditioning ethnic cleavage turns to be devoted to language. The author gives a very persuasive introduction to this problem as well as promotes an exclusive comparison where the Western (arguably – civilly developed cultures) and Central-Eastern European nations, as well as history-influenced modifications to the character of the issue, are paralleled. We are not presented with a narrow and simplistic narration but are rather compelled to thoroughly perceive the multilateral complexity of this problem. Hence the author tries to trace the solutions that entail inter-ethnic tensions, although he primarily identifies the 'true' causes for such tensions. Schopflin finds it necessary to define what exactly ethnicity is and the reasons why language is enacted to such a salient role in ethnic self-consciousness.